DESIGNING INNOVATIVE APPLICATION INTERFACES FOR CHINESE CULTURAL PRODUCTS: STRATEGIES TO ATTRACT USERS, STREAMLINE ORDERING, AND PROMOTE EXPORTS THROUGH INTERFACE INNOVATION - Yang, Ruo Ting (2025)
Against the backdrop of globalization and thriving cultural trade, the export of Chinese cultural products faces a dual challenge of expanding international markets and enhancing competitiveness. This Dissertation focuses on designing an innovative digital platform interface aimed at effectively integrating cultural connotations with modern technology, meeting the needs of international users, and promoting the dissemination and trading of cultural products. By analyzing the Strategies to Attract Users, Streamline Ordering, and Promote Exports through Interface Innovation, cross-cultural interface design strategies are proposed. The core functions of the platform include cultural product display, online transactions, user interaction, and multilingual support, and the information architecture has been optimized to adapt to different cultural backgrounds. Visual design incorporates traditional Chinese colors and cultural symbols, while also considering the visual adaptability of global users. The study used prototype tools to build interfaces and optimized them through usability testing. The achievements not only provide practical interface design solutions for the export of cultural products, which are expected to improve the display effect and sales conversion rate in the international market, but also provide theoretical references for the development of digital cultural platforms, and help promote the dissemination and exchange of Chinese culture on a global scale.